Direct and indirect effects of native range expansion on soil microbial community structure and function. (September 2016) - Collins, Courtney G.; Carey, Chelsea J.; Aronson, Emma L.; Kopp, Christopher W.; Diez, Jeffrey M.
Summary: Analogous to the spread of non‐native species, shifts in native species' ranges resulting from climate and land use change are also creating new combinations of species in many ecosystems. These native range shifts may be facilitated by similar mechanisms that provide advantages for non‐native species and may also have comparable impacts on the ecosystems they invade. Soil biota, in particular bacteria and fungi, are important regulators of plant community composition and below‐ground ecosystem function. Compared to non‐native plant invasions, there have been relatively few studies examining how soil biota influence – or are influenced by – native species range shifts. Here, we examined how a native range‐expanding sagebrush species ( Artemisia rothrockii ) affects below‐ground abiotic conditions and microbial community structure and function using next‐generation sequencing coupled with other biotic and abiotic soil analyses. We utilized a range‐expansion gradient, together with a shrub removal experiment and structural equation models, to determine the direct and indirect drivers of these interconnected processes. Sagebrush colonization increased bacterial and archaeal richness and diversity and altered community composition across the expansion gradient. Soil organic C and N and soil moisture increased with sagebrush presence; however, results varied across the expansion gradient. We found no relationship between sagebrush and soil pH; however, pH strongly influenced microbial richness and diversity. Microbial (substrate‐induced) respiration was influenced by soil organic N, as well as microbial diversity and functional group relative abundances, highlighting direct and indirect effects of sagebrush on microbial community structure and function. Microbial community composition of soils after 4 years of sagebrush removal was more similar to communities in shrub interspaces than underneath shrubs, suggesting microbial community resilience. Synthesis . Our results suggest that native range expansions can have important impacts on soil biological communities, soil chemistry and hydrology which can further impact below‐ground ecosystem processes such as nutrient cycling and litter decomposition. The combination of high‐throughput sequencing and structural equation modelling used here offers an exciting yet underutilized approach to understanding how both native and non‐native species' range expansions may affect the structure and function of soil ecosystems. Abstract : Our results suggest that native range expansions can have important impacts on soil biological communities, soil chemistry and hydrology which can further impact below‐ground ecosystem processes such as nutrient cycling and litter decomposition. The combination of high‐throughput sequencing and structural equation modelling used here offers an exciting yet underutilized approach to understanding how both native and non‐native species' range expansions may affect the structure and function of soil ecosystems.